PWE-272 Concordance of non-invasive markers of liver fibrosis in a mixed population of liver diseases. (28th May 2012) - Trembling, P M; Cheung, M; Tanwar, S; Rosenberg, W M
Abstract : Introduction: The enhanced liver fibrosis (ELF) test, a panel of liver fibrosis biomarkers, accurately assesses fibrosis in a range of chronic liver disease (CLD) aetiologies. We evaluated concordance of ELF and transient elastogrpahy (TE) in assessing fibrosis in a cohort of mixed aetiology CLD in our clinic. Methods: Patients who had undergone ELF testing and TE within 1-year for investigation of CLD were identified. Data derived thresholds for ELF were used to identify moderate fibrosis and cirrhosis with 90% sensitivity and specificity respectively. TE thresholds were based on a study of patients with mixed viral aetiology CLD with the same sensitivities/specificities. 1 Valid TE criteria: success rate ≥60%, median stiffness IQR ≤30%. ELF test was included in routine blood testing. TE was performed in 8 min on average by an experienced nurse. Concordance with ELF and TE classification was calculated. In addition patients who had undergone ELF testing or TE with liver biopsy within 2 years were identified. Histological fibrosis severity was evaluated and agreement with ELF/TE calculated. Results: Of 110 consecutive patients, 99 had ELF/TE within 1-year. Median age 50 (22–80). Aetiology: HCV 46%, HBV 25%, unknown 17%, fat 7%, PBC 1%, HBV/HCV 1%, α-1 antitrypsin deficiency 1%, normal 1%. No ELF tests failed. TE failed in 11%, and valid results obtained in 66% and ELF/TE concordance analysis based on these. Correlation between ELF and TE was 0.6. The Abstract PWE-272 table 1 shows distribution of patients for mild, moderate-severe fibrosis and cirrhosis. Agreement between ELF/TE; κ=0.18. Prediction of moderate fibrosis, κ=0.14, with 34% discrepancy. Prediction of cirrhosis, κ=0.49, with 17% discrepancy. Analysis of the notable mild TE/moderate ELF group shows a negative skew of TE (mean 4.13, median 4.30) and a positive skew of ELF (mean 8.44, median 8.37). Clinical correlation of discrepant cases for cirrhosis indicates consistency with ELF in 13% (mod TE/cirrhosis ELF), and 67% (mod ELF/cirrhosis TE). Kappas for agreement with histology for moderate fibrosis and cirrhosis were, for ELF: 0.19, 0.71 (n=16); for valid TE: 0.13, 0.79 (n=11). Conclusion: In a cohort of mixed aetiology CLD, ELF was more reliable than TE in generating a result with a failure rate of 34% for TE. Agreement between ELF and TE increased with fibrosis severity. The mild/moderate discordance suggests a need to review thresholds. When selecting non-invasive tests for use in busy clinics failure rate of the test and time taken to obtain a result should be considered. Competing interests: P Trembling: None declared, M Cheung: None declared, S Tanwar: None declared, W Rosenberg Grant/Research Support from: Siemens Healthcare Diagnostics. Reference: 1. Degos F, Perez P, Roche B, et al. Diagnostic accuracy of FibroScan and comparison to liver fibrosis biomarkers in chronic viral hepatitis: a multicenter prospective study (the FIBROSTIC study). J Hepatol 2010;53 :1013–21.